Generasi Milenial dan Moderasi Beragama: Promosi Moderasi Beragama oleh Peace Generation di Media Sosial - Elvinaro, Qintannajmia; Syarif, Dede (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
After its launching in 2019, the religious moderation program has taken on conventional methods of religious gathering, seminar, and discussion, whereas the millennial generation, one of main targets of this campaign, are active social media users and unacquainted with these methods. Employing virtual ethnography with a digital observation to social media platform and online interview, this paper aims to investigate the religious moderation program in digital sphere as a strategy to counter radicalism that circulate in the virtual sphere. By focusing its analysis on the digital messages on religious moderation circulated digitally by the Peace Generation movement, this paper argues that religious moderation campaign targeting millennial group should be implemented in media which millennial generation are accustomed to such as social media. The application of social media in religious moderation campaign is not only strategic in distributing the messages but also an attractive method in providing accessible alternative content for the millennial generation.